Characteristics of Lung Cancer Patients with Brain Metastases based on Baseline Head Computerized Tomography (CT)-scan in Arifin Achmad Hospital October 2022 - June 2023 - Sari, Rezki Permata; Fauzi, Zarfiardy Aksa; Simanjuntak, Arya Marganda (Indonesian Society of Respirology (ISR), 2024)
Background: The majority of lung cancer cases are often discovered at a late stage because it frequently develops without symptoms in the early stages. Many lung cancer deaths are caused by metastases to other organs. The purpose of this study was to examine the features of lung cancer patients with brain metastases using baseline CT scan data. Method: Between October 2022 and June 2023, a cross-sectional study was conducted at the Arifin Achmad Hospital in Pekanbaru on all newly diagnosed lung cancer patients with brain metastases who also met the inclusion and exclusion criteria. Results: Eight subjects of lung cancer with brain metastasis were found from 49 patients. All subjects were male with age mostly in between 40 and 60 years. Three subjects (37.5%) were Squamous Cell Carcinoma (SCC), four subject (50%) were adenocarcinoma and 1 (12.5%) were SCLC. Conclusion: This study discovered that 16.3% of patients who met the inclusion criteria had lung cancer with brain metastases. Further research should be done on a cohort study and a preventive strategy for lung cancer with brain metastases.